2020
DOI: 10.1111/apha.13563
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in insulin‐like growth factors signalling in mouse Leydig cells increase conversion of testosterone to estradiol because of feminization

Abstract: Aim A growing body of evidence pointed correlation between insulin‐resistance, testosterone level and infertility, but there is scarce information about mechanisms. The aim of this study was to identify the possible mechanism linking the insulin‐resistance with testosterone‐producing‐Leydig‐cells functionality. Methods We applied in vivo and in vitro approaches. The in vivo model of functional genomics is represented by INSR/IGF1R‐deficient‐testosterone‐producing Leydig cells obtained from the prepubertal (P21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…In conclusion, the results published by Radovic Pletikosic and colleagues 2 suggest that sexual differentiation might involve a direct effect of obesity‐related factors on the testis, and in particular on Leydig cells, through a modification of the expression of sex‐determination factors, even in adult animals . In light of these observations, sexual differentiation is likely more plastic than generally assumed and links the influence of environmental factors, metabolic fitness and health conditions to male physiology, metabolism and reproductive capacity (Figure 1).…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…In conclusion, the results published by Radovic Pletikosic and colleagues 2 suggest that sexual differentiation might involve a direct effect of obesity‐related factors on the testis, and in particular on Leydig cells, through a modification of the expression of sex‐determination factors, even in adult animals . In light of these observations, sexual differentiation is likely more plastic than generally assumed and links the influence of environmental factors, metabolic fitness and health conditions to male physiology, metabolism and reproductive capacity (Figure 1).…”
Section: Figurementioning
confidence: 78%
“…Correspondingly, the Insulin/Insulin‐like Growth Factor (IGF) pathway has been described as a key player of sexual development and reproduction 1 . In this issue, Radovic Pletikosic and colleagues demonstrated that Insulin/IGF signalling exerts its action through the regulation of steroidogenesis in Leydig cells 2 .…”
Section: Figurementioning
confidence: 99%
“…As for Trypan blue exclusion test, cell viability was greater than 95%. The controls to validate this purification method’s comprehensiveness were challenges of purified cells (although few of them) from the inter-layers with hCG ( 20 ). Briefly, the cells from the inter-layers (few of them) were collected following the described procedures and incubated with/without (10 ng/ml), but androgen production was not detected.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors consider this and have no limitations on which requests will be answered. 11 Only a few articles stating that primary data are available. 12 These examples highlight the limitations of open data, as every request needs to be answered equally.…”
Section: Open Research Data -Expectations and Limitationsmentioning
confidence: 99%